PENGEMBANGAN SOAL GEOMETRI DAN PENGUKURAN BERBASIS FRAMEWORK AKM MENGGUNAKAN KONTEKS SOSIAL BUDAYA DI SIDOARJO - Kholifah, Nur (JEDMA Jurnal Edukasi Matematika, 2024)
This study aims to develop geometry questions based on the AKM Framework using the socio-cultural context of Sidoarjo. The development method includes needs analysis, question design, expert validation, field trials, and product revision. As a result, 10 geometry questions were developed using batik motifs and temple structures in Sidoarjo as contexts. These questions demonstrated high internal validity (average 0.78-0.89) and external validity ( ). The internal reliability score was 0.764, and the external reliability was 0.979. A total of 83.3% of students scored above 76, indicating the questions' effectiveness in enhancing interest and understanding of geometry. The use of local socio-cultural elements made the learning process more meaningful and contextual, thus effectively improving the quality of mathematics education.